Three-factor model of the scale factor (SF) in the wear. Part 2 - Кузьменко, А.Г; Паламар, А.М. (Problems of Tribology, 2015)
Implemented method for constructing a three factor analytic models tribological processes. Wear test performed 4 pairs of friction. It has been established that the dependence of the wear of the contact area is linear.